2021
DOI: 10.5559/di.30.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Life Habits of Children and Young People during Social Isolation Caused by the COVID-19 Pandemic

Abstract: The aim of the study was to examine the habits of high school and primary school students related to diet and physical activity before and after the period of social isolation. Furthermore, the relationship between parents' attitudes about the importance of physical activity and their children's motivation to engage in it was examined. The online questionnaire was completed by 25,274 parents of primary school students and 5,169 high school graduates from the Republic of Croatia. The results show a trend of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A study conducted in a national sample involving 25,274 parents of grade 5 and grade 7 primary school students and 5169 grade 4 secondary school students found that the prevalence of participation in organized sports activities in 2020 was 54.0% among primary school students and 30.0% among secondary school students. 39 In a secondary analysis of data from a study conducted among 809 preschool children from Osijek, Rijeka, Split, and Zagreb macroregions (age: 5-7 y) in 2018/19, 24 we found a prevalence of participation in organized sports activities of 59.2%. Based on data for the year 2022 provided by the Croatian School Sport Federation, it was estimated that 38.6% of primary and secondary school students are members of school sports clubs.…”
Section: Organized Sport and Physical Activitymentioning
confidence: 78%
See 3 more Smart Citations
“…A study conducted in a national sample involving 25,274 parents of grade 5 and grade 7 primary school students and 5169 grade 4 secondary school students found that the prevalence of participation in organized sports activities in 2020 was 54.0% among primary school students and 30.0% among secondary school students. 39 In a secondary analysis of data from a study conducted among 809 preschool children from Osijek, Rijeka, Split, and Zagreb macroregions (age: 5-7 y) in 2018/19, 24 we found a prevalence of participation in organized sports activities of 59.2%. Based on data for the year 2022 provided by the Croatian School Sport Federation, it was estimated that 38.6% of primary and secondary school students are members of school sports clubs.…”
Section: Organized Sport and Physical Activitymentioning
confidence: 78%
“…[14][15][16][17][18][19][20][21][22][23][24] Of these, 18 studies were included in evidence synthesis. [14][15][16][17][18][19][20][21][22][23][24]34,39,47,51,62,69,70,76,81,84,90,100 The stages of search and study selection process are summarized in Figure 1. From the additional internet searches, we selected examples of key national-and county-level physical activity policies, programs, and infrastructure (Supplementary Tables S4 and S5 [available online]).…”
Section: Search and Study Selection Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that around 65 million children between the ages of 3 and 15 are directly affected by emergencies and protracted crises worldwide, meaning that they are at risk of lack of protection, disruption of education and displacement, as well as other psychosocial problems (Nicolai et al, 2015). In recent years, interest in researching crisis situations in the education system in the Republic of Croatia has significantly increased, especially during and after the pandemic (e.g., Ristić Dedić & Jokić, 2021;Ćurković et al, 2021;Zovko et al, 2022;Ristić Dedić et al, 2023). In Croatia, coinciding with the outbreak of COVID-19 in March 2020, there were a series of earthquakes that disrupted daily school operations and affected general safety.…”
Section: Introductionmentioning
confidence: 99%